Підготовка фахівців третього рівня освіти нафтогазового профілю: особистісні імперативи науковця в умовах глобалізації - Скальська, Дарія; Процюк, Василь; Skalskaia, D.; Protsiuk, V. (Східноєвропейський національний університет імені Лесі Українки, 2016)
У статті розкрито шляхи формування особистісних та професійних імперативів науковців нафтогазового профілю під час їхньої підготовки як фахівців третього рівня освіти. Обґрунтовано та доведено необхідність виконання програмних вимог навчального курсу «Філософія» для отримання науковцями загальнонаукових (філософських) компетентностей в умовах глобалізаційних освітніх процесів. The article actualizes the recognition of the fact that the professionals of the third education level should have philosophical skills in explicating the world. In particular, this concerns the academic staff of the oil and gas complex. In order to form and develop their personal imperative qualities as scholars, they should master the philosophy and methodology of the scientific cognition, up-to-date information technologies and constantly improve their professional skills, as it is required by the enhanced energy security of the country. In the context of the ever-changing world view, the scientific work of the representatives of the oil and gas industry is in direct relation to their philosophical competences, personal priorities and willingness to make important decisions. Gaining higher qualification of the third education level assumes that postgraduates and degree-seeking students meet the requirements in the philosophically-methodological, praxeological, moral and ethical training necessary for their further successful scientific work. The article concretizes the globalization tendencies in training of the new generation of scholars that will provide the country with the creative, value-oriented engineering intelligentsia, good at innovative technologies.
Training of Specialists of the Third Education Level of Oil and Gas Profile: Personal Imperatives of Scholars in the Age of Globalization
Keywords: третій рівень освіти; third education level; філософія; нафтогазова галузь; особистісні імперативи; глобалізаційні процеси; філософські компетентності; philosophy; oil and gas industry; personal imperatives; globalization processes; philosophical competences